Cryptanalysis of CIKS-128 and CIKS-128H Suitable for Intelligent Multimedia and Ubiquitous Computing Systems - Lee, Changhoon; Kim, Jongsung; Sung, Jaechul; Lee, Yang Sun; Lee, Chang Hoon (COMPUTING AND INFORMATICS, 2012)
Recently, data-dependent permutations (DDP) that are very suitable for intelligent multimedia and ubiquitous computing systems have been introduced as a new cryptographic primitive for the design of fast encryption systems. The CIKS-128 and CIKS-128H block ciphers are the typical examples of DDP-based encryption algorithms. In this paper, we show that CIKS-128 and CIKS-128H are vulnerable to related-key differential attacks. We first describe how to construct their full-round related-key differential characteristics with high probabilities and then we exploit them to break the full-round CIKS-128 and CIKS-128H with 2^44, and 2^48 data/time complexities, respectively.